CRISPR–Cas9-mediated nuclear transport and genomic integration of nanostructured genes in human primary cells. Issue 3 (1st February 2022) - Lin-Shiao, Enrique; Pfeifer, Wolfgang G; Shy, Brian R; Saffari Doost, Mohammad; Chen, Evelyn; Vykunta, Vivasvan S; Hamilton, Jennifer R; Stahl, Elizabeth C; Lopez, Diana M; Sandoval Espinoza, Cindy R; Deyanov, Alexander E; Lew, Rachel J; et al.
Abstract: DNA nanostructures are a promising tool to deliver molecular payloads to cells. DNA origami structures, where long single-stranded DNA is folded into a compact nanostructure, present an attractive approach to package genes; however, effective delivery of genetic material into cell nuclei has remained a critical challenge. Here, we describe the use of DNA nanostructures encoding an intact human gene and a fluorescent protein encoding gene as compact templates for gene integration by CRISPR-mediated homology-directed repair (HDR). Our design includes CRISPR–Cas9 ribonucleoprotein binding sites on DNA nanostructures to increase shuttling into the nucleus. We demonstrate efficient shuttling and genomic integration of DNA nanostructures using transfection and electroporation. These nanostructured templates display lower toxicity and higher insertion efficiency compared to unstructured double-stranded DNA templates in human primary cells. Furthermore, our study validates virus-like particles as an efficient method of DNA nanostructure delivery, opening the possibility of delivering nanostructures in vivo to specific cell types. Together, these results provide new approaches to gene delivery with DNA nanostructures and establish their use as HDR templates, exploiting both their design features and their ability to encode genetic information. This work also opens a door to translate other DNA nanodevice functions, such as biosensing, into cell nuclei.